Integrating Visual Media in the Development of Islamic Religious Education at Raudlatul Athfal Hidayatus Sibyan, East Lampung - Siti Ropingatun; Oon Rohayati; Rifaatul Maimunah; Qurotul A'yuni; Siti Nurbiyah; Ahmad Nur Husaini (Journal of Research in Islamic Education, 2025)
This study aims to describe: (1) the use of visual media in the development of Islamic Religious Education learning at Raudlatul Athfal Hidayatus Sibyan in Pematang Tahalo; (2) the supporting factors for the use of visual media in enhancing IRE learning at the institution; and (3) the inhibiting factors that hinder the implementation of visual media in IRE instruction at Raudlatul Athfal Hidayatus Sibyan. This research adopts a descriptive qualitative approach. Data were collected through observation, interviews, and document analysis. The subjects of the study consisted of the school principal, teachers, and students. The data analysis techniques employed include data reduction, data presentation, conclusion drawing, and verification. The results of the study reveal the following: (1) The visual media used in IRE instruction included still images such as posters, caricatures, and cartoons, as well as motion pictures. The use of such media has enhanced the quality of the teaching and learning process. (2) The supporting factors in utilizing visual media include the professionalism of teachers, which is reflected in their preparation of materials, methods, media, instruction, and evaluation; students’ strong curiosity; the school leadership’s empathetic support for program implementation; and active parental involvement and cooperation all of which are vital to the school’s success. (3) The inhibiting factors include the limited availability of visual data or media that align with the full range of IRE content particularly suitable motion pictures; the diverse intellectual backgrounds of students; and, at times, the inadequate preparation of instructional tools by teachers, which requires considerable diligence and thoroughness.